Methanhydrate in arktischen Sedimenten – Einfluss auf Klima und Stabilität der Kontinentalränder - Bohrmann, Gerhard; Treude, Tina; Wallmann, Klaus J. G. (Wissenschaftliche Auswertungen, 2014)
Methane hydrates in marine sediments – Impact on climate and stability of continental slopes: The Arctic Ocean increasingly gets into the focus of methane hydrate research with respect to Global Warming. In the cold Arctic Ocean, hydrates are stable at relatively shallow water depths, and due to rapidly increasing water temperatures this region is considered to become a major source of atmospheric methane in the near future. But many factors, which are essential to make solid predictions about the fate and consequences of hydrate-related methane in the Arctic, still remain unclear. Uncertainties range from the size of the Arctic methane hydrate inventory to the efficiency of microbes to consume methane that is liberated in sediments and migrating through the water column. A potential collateral impact of massive gas hydrate destabilization could be failures of Arctic continental slopes with resulting mass wasting and tsunami formation. Although the correlation between hydrates and mass wasting are still a matter of debate, historic events have been identified and their causes are part of ongoing research. This book chapter will provide an overview of most recent research and discussions about Arctic gas hydrates and its fate in the light of Global Warming.